The Effect of Creativity, Self-Efficacy, And Workload on Employee Performance at Jaens Spa Ubud, Bali - Maharani, Ni Ketut Sinta Santania; Puspitawati, Ni Made Dwi; Parwita, Gde Bayu Surya (EMAS, 2026)
This study aims to examine and analyze the extent to which servant leadership, interpersonal communication, and knowledge sharing contribute to improving employee performance at Smoke.Bali Restaurant, located in Badung Regency, Bali. Using a quantitative approach, this study involved all 42 employees as respondents through a total census technique. Data collection was conducted using a questionnaire that adopted a five-point Likert scale, then processed using multiple linear regression analysis through SPSS software. The main findings show that the three independent variables, both partially and simultaneously, have a positive and significant effect on employee performance. The Adjusted R Square value reached 0.679, indicating that approximately 67.9% of employee performance variability can be explained by the combination of servant leadership, interpersonal communication, and knowledge sharing, while the rest is influenced by other factors outside the model. The beta coefficients for each variable were 0.448 for servant leadership (p < 0.001), 0.513 for interpersonal communication (p < 0.001), and 0.546 for knowledge sharing (p < 0.001). These results are consistent with PathGoal Theory and a number of previous empirical studies, which confirm the important role of servant leadership, effective communicative interaction, and a culture of knowledge sharing in the context of the competitive hospitality industry. Practical implications for restaurant management include developing servant leadership training programs, optimizing internal communication channels, and initiatives to encourage knowledge exchange among employees to achieve more optimal operational performance.